Thermal Hydraulic Evaluation of a proposed annular Fuel for VVER1000 Reactor (Journal of Nuclear Technology in Applied Science, 2024)
Thorium based fuel is a promising fuel as it reduces the radiation protection cost of safety and improves the fuel performance with high burnup capability. In this paper the core of VVER-1000 nuclear reactor is designed with (Th0.9U0.1) O2 annular fuel rod for internally and externallycooled (dual cooled) fuel. Thermal performance of the present case is analyzed using ANSYS CFD code. Equivalent cell including a fuel rod and its surrounding coolant within a hexagonal assembly in the hot channel is simulated to get the maximum fuel temperature and maximum clad temperature. The results are compared with the calculated results obtained for the conventional UO2 fuel rod. Critical Heat Flux (CHF) and minimum DNBR are obtained and validated. The results indicated that the maximum fuel temperature of (Th0.9U0.1) O2 annular fuel is lower than that of the UO2 fuel by about 530oK. Lower maximum temperature and flatten temperature distribution in the thorium-based annular fuel rod provides more thermal safety margin in the reactor.
Keywords: Annular fuel; VVER-1000; ANSYS; Thermal Hydraulic of Thorium Based Fuel